Abrasive Materials (MATERIALS MINERALS YEARBOOK-1978) - W. T. Adams (The National Institute for Occupational Safety and Health (NIOSH), 1978)
The production of natural abrasives var¬ied in quantity and value compared with 1975. Output of tripoli-type materials and garnet increased in both quantity and value; special silica stone products decreased in quantity and increased in value; the production of emery decreased. The production and value of manufactured abrasive materials increased for all types. [ ]